Electronic system to speckle phenomenon characterization for random movement on fiber optics - Ortega Galicio, Orlando Adrian; Calvo, Jinmi Lezama; Diaz Leyva, Teodoro Neri; Saavedra, Melina Machaca; Sanchez Lopez, Simon Alejandro; Baldárrago, Alexandra Chávez; Atalaya, Omar Chamorro (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Peru is a country located in a telluric area. The early detection of earthquakes will alert the population and avoid human losses. There are different methods to detect it, mainly on mechanical movements and electronic sensors, which are currently used. This article presents the analysis and implementation of a repetitive motion generation and detection system based on the study of the speckle phenomenon through an optical fiber. The analysis is calculated by the technique of averaged difference that allows obtaining the intensity variation of two consecutive frames, as the speckle pattern changes and occupies different positions. Several tests are carried out that show the relationship of the controlled random movement and speckle characteristics obtained, the test system that can be used for the detection of random movements similar to P and S earthquakes waves.